PENGARUH KEBIJAKAN DISIPLIN PNS TERHADAP KINERJA BIROKRASI (SUATU STUDI KECAMATAN SALIBABU KABUPATEN KEPULAUAN TALAUD) - Tatangin, Tuhayati (Universitas Sam Ratulangi, 2013)
Purpose of this study was to determine the effect of policy discipline civil servants to the improved performance of existing government apparatus in the district Salibabu The method used in this study is the method kuantitatif.dan type of data collected regarding the discipline policy variables and the variable performance of the civil service apparatus is the primary data is data that comes directly from research subjects or responden.selain was also collected secondary data is data that has been collected by other parties or sourced from related documents.Keywords: foreigh, performance